2015
DOI: 10.1089/wound.2015.0646
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Therapies for Scar Prevention

Abstract: Significance: There are *12 million traumatic lacerations treated in the United States emergency rooms each year, 250 million surgical incisions created worldwide every year, and 11 million burns severe enough to warrant medical treatment worldwide. In the United States, over $20 billion dollars per year are spent on the treatment and management of scars. Recent Advances: Investigations into the management of scar therapies over the last decade have advanced our understanding related to the care of cutaneous s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
48
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 67 publications
0
48
0
2
Order By: Relevance
“…However, past and current antiscarring therapies have met limited success. 31 We indeed found that P311 production is switched on in healing wounds and normal and hypertrophic scars compared with normal skin, in which it is absent, indicating a potential role for P311 in scar formation. Indeed, in vivo and in vitro studies indicated that, because of its stimulation of TGF-b1 to -b3 translation, P311 is required for collagen deposition and tensile strength during normal scar formation which, in turn, is essential to prevent scar dehiscence.…”
mentioning
confidence: 52%
“…However, past and current antiscarring therapies have met limited success. 31 We indeed found that P311 production is switched on in healing wounds and normal and hypertrophic scars compared with normal skin, in which it is absent, indicating a potential role for P311 in scar formation. Indeed, in vivo and in vitro studies indicated that, because of its stimulation of TGF-b1 to -b3 translation, P311 is required for collagen deposition and tensile strength during normal scar formation which, in turn, is essential to prevent scar dehiscence.…”
mentioning
confidence: 52%
“…Intralesional corticosteroid injections with supplementary cryotherapy are first-line therapy for the treatment of keloids. 2,39 In 1977, the combination of corticosteroids and cryosurgery was introduced and detailed information on the method provided. 36 Despite the lack of objective parameters, the promising results led to the establishment of this method.…”
Section: Discussionmentioning
confidence: 99%
“…However, therapy depth in skin is limited due to high scattering of light in skin, causing a fundamental impediment for this technology (Preissig et al 2012). Cryotherapy, historically limited to small scar volumes (Block et al 2015), improved in the recent years and up to 51% reduction of the scar size after a single treatment have been reported (Har-Shai et al 2008). Different types of radiotherapy, such as Brachytherapy, X-ray, and electron beam have been used for scar treatments; however, these technologies require special heavy equipment and need to be used carefully to avoid carcinogenesis (Block et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Cryotherapy, historically limited to small scar volumes (Block et al 2015), improved in the recent years and up to 51% reduction of the scar size after a single treatment have been reported (Har-Shai et al 2008). Different types of radiotherapy, such as Brachytherapy, X-ray, and electron beam have been used for scar treatments; however, these technologies require special heavy equipment and need to be used carefully to avoid carcinogenesis (Block et al 2015). In contrast to the currently used physical therapies discussed above, for electroporation-based therapies, the distribution of the electric fields depends on the electrical properties of tissues such as resistance and capacitance (Golberg et al 2015a).…”
Section: Discussionmentioning
confidence: 99%